Local currency sovereign debt markets, global financial conditions and the role of foreign investors - Guilherme Suedekum (Graduate Institute of International and Development Studies, 2023)
This paper studies how the presence of foreign investors in local currency sovereign debt markets contributes to the transmission of global financial conditions to emerging market economies. My estimations indicate that the higher the share of local currency government bonds held by foreign investors, the more sensitive the credit risk of these bonds becomes to global financial shocks. When foreign investors' holdings reach 45 percent, the credit risk of local currency government bonds becomes as sensitive to global financial shocks as the credit risk of foreign currency government bonds. I also explore exogenous foreign investor outflows caused by an unanticipated announcement of country weight rebalancing in the J.P. Morgan GBI-EM Global Diversified index in March 2014. Countries that experienced foreign investor outflows also experienced a decrease in the sensitivity of their local currency sovereign debt markets to changes in global financial conditions.
Keywords: F34; G15; H63; 330; Emerging Market Economies; Local Currency Sovereign Debt; Credit Risk; Global Financial Conditions